2006
DOI: 10.1509/jmkg.2006.70.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Consumer Responses to Product Risk Information

Abstract: Two experiments examine how message framing moderates consumer responses to product risk information. The findings suggest that contrary to an influential theory, consumers exposed to loss-framed messages exhibit a general aversion to product risk involving both short-term adverse effects and more permanent harm. In contrast, consumers exposed to gain-framed messages differentiate among different types of product risk. They essentially ignore temporary product risks but give considerable decisional weight to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 40 publications
3
64
0
1
Order By: Relevance
“…As several authors have done before us (Cox et al, 2006;O'Keefe & Jensen, 2006), we argue that the tenets of the risk-framing hypothesis are flawed. Even if its predictions are partly supported by empirical evidence, the model simply does not deliver a satisfactory explanation of these findings.…”
Section: Perceived Risk and Message Framing: A Theoretical Critiquementioning
confidence: 81%
See 1 more Smart Citation
“…As several authors have done before us (Cox et al, 2006;O'Keefe & Jensen, 2006), we argue that the tenets of the risk-framing hypothesis are flawed. Even if its predictions are partly supported by empirical evidence, the model simply does not deliver a satisfactory explanation of these findings.…”
Section: Perceived Risk and Message Framing: A Theoretical Critiquementioning
confidence: 81%
“…Some authors have criticised the notion that the risk associated with the advocated behaviour determines the relative effectiveness of gain-and loss-framed messages, both on empirical and on theoretical grounds (Cox, Cox, & Zimet, 2006;O'Keefe & Jensen, 2006). However, it should be noted that the momentum of the risk-framing hypothesis has not been slowed by those previous criticisms.…”
mentioning
confidence: 99%
“…However, we believe that under certain circumstances, consumers' actual weighting of severity and likelihood information will deviate markedly from these expected utility models-the perception of risk may be dependent on other elements of the situation. Risk may be evaluated relative to the perceived benefit (Alhakami and Slovic 1994;Finucane et al 2000) or influenced by the frame in which the message is presented (Cox, Cox, and Zimet 2006). Weinstein (2000, p. 65) notes that "it is surprising that empirical studies of health-protective behavior provide little support for a perceived probability by perceived severity interaction."…”
Section: Weighing the Severity And Likelihood Of Adverse Product Eventsmentioning
confidence: 99%
“…Other studies suggest that consumers often ignore risk disclosures (e.g., Menon et al 2003), and some have even suggested that such risk statements can actually enhance consumers' product evaluations (e.g., Goetzl 2000). More recent research has suggested that consumers subjectively evaluate product risk statements depending on whether statements of product benefits are gain or loss framed (Cox, Cox, and Zimet 2006). However, little is known about the contingencies that govern whether advertised risk disclosures have a negative, neutral, or positive impact on consumer brand attitudes and intentions.…”
mentioning
confidence: 99%
“…Last part of the survey is about participants' descriptive information such as age, gender, marital status, education level, employment status and income per month. Cox and Cox (2001), Cox, Cox and Zimet (2006), Cox (1967), Dowling and Staelin (1964), Roselius (1971) Online Shopping Intention (Ajzen and Fishbein, 1977) Personal Innovativeness Agarwal and Prasad (1998) Population of the research contains individuals that buy goods and services online in Turkey. A sample of 280 university students in Turkey has been selected by Convenience sampling method.…”
Section: Methodsmentioning
confidence: 99%